Memotret Akuntabilitas Wakaf Aulad Di Minangkabau : Studi Kasus Praktik Wakaf Aulad Di Kabupaten Agam Sumatera Barat - Annisa Ramadhani; Eliyanora; Yossi Septriani (Akuntansi dan Manajemen, 2016)
Waqf is one of the economic mechanisms of Islam that has the potential to increase economic strength and welfare of the people. Waqf for the welfare of the family and closest family (waqf aulad) is highly recommended in Islam. Asset ability of aulad waqf to be potentially productive cannot be separated from the hands of a nadzir as a waqf manager. To realize optimal management of waqf aulad, management is needed based on the principle of accountability. This study aims to see how accountability of Nadzir as a manager of waqf aulad in Minangkabau. Then, Nadzir's accountability seen from the accountability mechanism summarized by Roberts (1996) is a sense of self accountability, representative accountability, individual management and accounting for independence. The author observes the form of waqf aulad accountability by using a qualitative research case study approach in Lubuk Basung sub-district, Agam Regency, West Sumatra. The author analyzes the findings using inductive data analysis and checks the validity of the data using data triangulation techniques. Judging from the accountability mechanism summarized by Roberts, the sense of self accountability, representative accountability, individual management is good. Judging from the accountability mechanism summarized by Roberts, the sense of self accountability, representative accountability, individual management is good. The weakness of Nadzir is the implementation of accounting for independence.